Determinants of Risk in Indonesian Islamic Banking: An Empirical Investigation - Haryanto, Sugeng; Safriliana, Retna; Ridloah, Siti; Ariefudin, Muhammad Umar; Khotimah, Lidia Khusnul (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2024)
Islamic banking has witnessed significant growth globally, including in Indonesia, with expansions in both fund mobilization and financing activities. This study analyzes the determinants of risk in Indonesian Islamic banks from 2009 to 2022, focusing on the effects of financing-to-deposit ratio (FDR), financing growth, efficiency, company size, capital adequacy ratio (CAR), and third-party fund (DPK), on non-performing financing (NPF). Utilizing unbalanced panel data and multiple linear regression, the research finds that financing growth and efficiency have negligible effects on risk. In contrast, FDR, company size, CAR, and DPK significantly influence it. Higher FDR is linked to increased risk, while larger banks and higher CAR are associated with reduced risk. The results suggest that Islamic banks should balance financing and deposits to manage risk effectively and emphasize the importance of efficient operations and sustainable growth. This research is limited to the internal aspects of banks as determinants of FDR. Future research could examine external factors and alternative risk measures to deepen the understanding of risk in Islamic banking.==============================================================================================================ABSTRAK – Determinan Risiko Perbankan Syariah di Indonesia: Suatu Kajian Empiris. Perbankan syariah mengalami pertumbuhan yang signifikan secara global, termasuk di Indonesia, terutama dalam hal mobilisasi dana dan aktivitas pembiayaan. Studi ini menganalisis faktor-faktor penentu risiko pada perbankan syariah di Indonesia periode 2009 - 2022. Secara spesifik, kajian ini menguji pengaruh FDR, pertumbuhan pembiayaan, efisiensi, ukuran perusahaan, CAR dan DPK terhadap pembiayaan bermasalah. Dengan menggunakan data panel tidak seimbang (unbalance) dan regresi linier berganda, penelitian ini menemukan bahwa pertumbuhan pembiayaan dan efisiensi tidak memiliki pengaruh yang signifikan terhadap risiko. Sebaliknya, FDR, ukuran perusahaan, CAR, dan DPK memberikan pengaruh yang signifikan terhadapnya. FDR berkorelasi positif dengan peningkatan risiko, sementara ukuran perusahaan dan CAR berkorelasi negatif dengan pengurangan risiko. Kajian ini menyarankan agar bank-bank syariah menyeimbangkan antara pembiayaan dengan simpanan sehingga dapat mengelola risiko secara efektif dengan penekanan pada efisiensi operasional dan pertumbuhan berkelanjutan. Penelitian ini dibatasi pada aspek internal bank sebagai determinan FDR. Penelitian selanjutnya dapat mengkaji faktor-faktor eksternal dan ukuran risiko alternatif untuk memperdalam pemahaman tentang risiko dalam perbankan syariah.